Orbital stability of periodic standing waves of the coupled Klein-Gordon-Zakharov equations - Qiuying Li; Xiaoxiao Zheng; Zhenguo Wang (AIMS Mathematics, 2023)
This paper investigates the orbital stability of periodic standing waves for the following coupled Klein-Gordon-Zakharov equations